Challenges facing in Organizing Modern Geography Textbooks using Dewey Decimal Classification System: An analytical study - Visakaruban, M.; Poologanathan, P.; Sajanthan, K.; Kesavan, Y. (Sri Lanka Library Association, 2022)
The Dewey Decimal Classification System is the basic standard used to organize the information resources collected in libraries. This classification method organizes the universal knowledge using Hindu-Arabic numerals from 000 to 999. In this regard, there are some problems in organizing Geography textbooks. Especially today; the Geography curriculum found in the University curriculum has expanded and developed into an Interdisciplinary Science filed that incorporates various other disciplines. However, the Geography textbooks cannot be organized into a single volume within the given numerical codes 910 and 913-919, which was refered by the Dewey Decimal Classification System. Modern Geography textbooks are not organized in a number construction like Philosophy, Religion and Art. For example, the branches of Human Geography include Political Geography; Cultural Geography and Economic Geography, which have to be organized under the main category of Social Science (300). Similarly, the main branches of Physical Geography are Topography, Geomorphology and Meteorology, Climate Geography, Atmosphere and Rocks, and Oceanography have to be organized under the main category of Science (500). The primary purpose of this study is to identify the Geographical textbooks scattered in different places and propose strategies that will make it easier for the reader to meet their needs. For this research, descriptive methods were used. This study recommends that the library shall develeop and maintain an ‘Athority File of Subject Headings’ to organize the Geography Textbooks. Particulalrly this research concludes that organizing Geography textbooks under the Class code 550 will be a solution to bring the Geography textbook under one umbrella for the readers rather than organizing the Geography textbooks under the DDC’s given main category (910).
Keywords: Geography; Human Geography; Physical Geography; Deweydecimal classification System; Climate Geography